Innovative Eco-Porous Paver Materials as a Sustainable Approach with Recycled Tyres and Polyurethane - Azani, Nornishah; Abdullah, Mohd Sufyan; Kosnin, Hilmi (Progress in Engineering Application and Technology, 2026)
This paper will help to consider Crumb Rubber (CR) with Polyurethane Binder (PU) as one of the sustainable materials for porous pavers besides increasing tire waste. Three mix ratios were considered: Sample A (90% CR : 10% PU), Sample B (80% CR : 20% PU) and Sample C (70% CR : 30% PU). The eco-porous paver samples are tested for water permeability test (ASTM D2434) and slip resistance test (ASTM E303-93). All mixes attained minimum standard values of British Pendulum Number, however, the permeability coefficients are much below the required limits. The results clearly state mechanical, environmental and economical aspects or benefits of using tire waste in constructions related to Sustainable Development Goals (SDGs) 9, 11 and 15 besides potentials for urban infrastructure and green building applications.